Potential treatment for chronic myeloid leukemia using microRNA: In silico comparison between plants and human microRNAs in targeting BCR-ABL1 gene - Syarifah Faezah Syed Mohamad; Marjanu Hikmah Binti Elias (Springer, 2024)
Indexed by WOS/SCOPUS